Colistin Susceptibility and Plasmid Mediated mcr-1 Gene Prevalance among Multi Drug Resistant Clinical Isolates of Escherichia coli, Kebsiella pneumoniae and Pseudomonas aeruginosa - A Hospital Based Cross Sectional Study - Nivetha Subramanian; Mangaiyarkarasi Thiyagarajan; Udhayasankar Ranganathan; Sunil S Shivekar; R Gopal (Journal of Medical Sciences and Health)
Introduction: The treatment options for multi drug resistant (MDR) and extensively drug resistant (XDR) Gram negative bacterial infections are limited. Colistin based combination therapy remains the last option for such infections. The emerging resistance to colistin, especially the transferrable mcr-1 gene mediated resistance poses a global threat. Objectives: This study aims to determine the colistin susceptibility among the multi drug resistant (MDR) clinical isolates of Escherichia coli, Kebsiella pneumoniae and Pseudomonas aeruginosa and also to determine the prevalence of mcr-1 gene in the plasmids of colistin resistant isolates. Materials And Methods: This cross-sectional hospital-based study was conducted in 2021. Colistin broth disk elution and colistin agar dilution methods were used to determine the colistin susceptibility of MDR clinical isolates. Plasmid DNA was isolated from colistin-resistant isolates by alkaline lysis, and conventional PCR was performed to detect the mcr-1 gene. Statistical Analysis: Statistical analysis was performed using SPSS software version 2.7. The results are presented in tables and charts. Results: In total, 124 MDR isolates were included in this study. Among the 124 isolates, 12 (9.6%) were found to be resistant to colistin using phenotypic methods. PCR for plamid mediated mcr-1 gene was negative in all 12 MDR isolates. Conclusion: Colistin resistance is relatively less among the MDR clinical isolates in our study. Transferable colistin resistance due mcr-1 gene mutation is not detected among colistin resistant isolates. Hence, colistin can be used with caution adapting the national and international guidelines in situations where most of the other antibiotics are resistant.